Hubungan Indeks Massa Tubuh, Hemoglobin, Hematokrit Pendonor dengan Kualitas Darah - Dwi Eni Danarsih; Praptana Praptana (Jurnal Kesehatan Amanah, 2025)
The quality of blood products, particularly Packed Red Cells (PRC), is a crucial factor in ensuring safe and effective blood transfusions. Donor conditions are thought to influence the quality of produced blood components, including factors such as Body Mass Index (BMI), hemoglobin (Hb), and hematocrit levels. This study aimed to analyze the relationship between donor BMI, hemoglobin, and hematocrit levels with the quality of PRC products, which include PRC volume, hemoglobin content, and hematocrit. This was an analytical observational study with a cross-sectional design, involving 30 blood donors at the Blood Transfusion Unit of the Indonesian Red Cross (PMI) in Gunungkidul. Donor BMI was calculated from weight and height measurements, while hemoglobin and hematocrit levels were examined from capillary blood samples. The volume, hemoglobin, hematocrit, and physical appearance of PRC were evaluated according to standard procedures and analyzed using the Pearson correlation test at a 95% confidence level (α = 0.05). The results showed that the donors had an average BMI of 26.58 kg/m², hemoglobin 14.62 g/dL, and hematocrit 43.17%. Meanwhile, the PRC units had an average volume of 200.76 mL, hemoglobin content of 37.38 g/unit, and hematocrit of 54.33%, with all plasma samples appearing clear. Statistical analysis revealed no significant correlation between donor BMI, hemoglobin, and hematocrit with PRC volume (p>0.05), PRC hemoglobin (p>0.05), or PRC hematocrit (p>0.05). These findings indicate that variations in donor BMI and baseline hematological parameters do not affect the quality of PRC products. This study concludes that donor BMI, hemoglobin, and hematocrit are not associated with PRC quality. Future studies are recommended to include additional parameters, such as triglyceride levels, to provide a more comprehensive understanding of donor factors affecting blood product quality.